Total Jamur, Jenis Kapang dan Khamir Pellet Ayam Kampung Super dengan Penambahan Berbagai Level Pollard Berprobiotik - Muhammad Nurdianto; Cahya Setya Utama; Sri Mukodiningsih (Agricultural Faculty, 2015)
(Total fungi, type of mold and yeasts in super native chicken pelleted feed with various level of probiotic pollard)ABSTRACT. The research objective is assessing the effect of adding various level of probiotic pollard on total fungi, type of mold and yeast. The material used in this research were fermented vegetables waste , molasses, distilled water, pollard, super native chickens feed, physiological NaCl (0.85% NaCl) and sabaroud glucose agar (SGA). Research using completely randomized design with 4 treatments and 4 replications. The treatment used were T0 = 100% feed + 0% probiotic pollard, T1 = 90% feed + 10% probiotic pollard, T2 = 80% feed + 20% probiotic pollard and T3 = 70% feed + 30% probiotic pollard. The observed parameters were total fungi, type of molds and yeast. The average of total fungi are 0 CFU; 0,55 x 107 CFU; 0,55 x 107 CFU and 0 CFU. Type of mold is Aspergillus niger and none yeast have grown. The conclusion is the addition of 10% and 20% probiotic pollard to super native chickens pellet yield mold type Aspergillus niger as much 0,55 x 107 CFU.